Health information technology in the international context - Menachemi, Nir; Singh, Sanjay Kumar, 1963- (Advances in health care management, 2012)
This volume focuses on management issues in the international context of health information technology (HIT). Nations around the globe have established policies designed to improve the computerization of their health care systems. It is believed that the adoption of HIT including clinical information systems, decision support systems, and networks or systems that facilitate the exchange of clinical and other health data will yield various desirable outcomes. These outcomes may include improvements in the quality of care, a reduction in medical errors, boosts in efficiencies, and improved provider and patient satisfaction. The purpose of this volume on HIT in the international context is to facilitate the exchange of management theory, best practice, implementation challenges, and the impact of adoption as it pertains to HIT adoption in one or more international settings. It offers a holistic viewpoint on health information technology use in health care organizations and systems, providing a managerial perspective from authors around the world that will prove useful for health care practitioners across a variety of settings.